1997
DOI: 10.1093/brain/120.3.515
|View full text |Cite
|
Sign up to set email alerts
|

Functional localization of the system for visuospatial attention using positron emission tomography

Abstract: PET was used to image the neural system underlying visuospatial attention. Analysis of data at both the group and individual-subject level provided anatomical resolution superior to that described to date. Six right-handed male subjects were selected from a pilot behavioural study in which behavioural responses and eye movements were recorded. The attention tasks involved covert shifts of attention, where peripheral cues indicated the location of subsequent target stimuli to be discriminated. One attention con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

98
456
7
13

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 860 publications
(574 citation statements)
references
References 6 publications
98
456
7
13
Order By: Relevance
“…Located in the inferior parietal lobule, the angular gyrus serves as a multimodal association area, facilitating mental processes such as arithmetic (Arsalidou & Taylor, 2011), visuospatial attention (Nobre et al., 1997), memory (Kim, 2010; Spaniol et al., 2009; Vilberg & Rugg, 2008) sequence learning (Rosenthal, Roche‐Kelly, Husain, & Kennard, 2009), and semantic processing (Benson et al., 2001; Obleser, Wise, Dresner, & Scott, 2007; Price, Peelle, Bonner, Grossman, & Hamilton, 2016; Price, 2012). Further, the posterior aspect of the angular gyrus serves as part of the default mode network (DMN), which is most active during rest or fixation and becomes deactivated when performing cognitive tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Located in the inferior parietal lobule, the angular gyrus serves as a multimodal association area, facilitating mental processes such as arithmetic (Arsalidou & Taylor, 2011), visuospatial attention (Nobre et al., 1997), memory (Kim, 2010; Spaniol et al., 2009; Vilberg & Rugg, 2008) sequence learning (Rosenthal, Roche‐Kelly, Husain, & Kennard, 2009), and semantic processing (Benson et al., 2001; Obleser, Wise, Dresner, & Scott, 2007; Price, Peelle, Bonner, Grossman, & Hamilton, 2016; Price, 2012). Further, the posterior aspect of the angular gyrus serves as part of the default mode network (DMN), which is most active during rest or fixation and becomes deactivated when performing cognitive tasks.…”
Section: Discussionmentioning
confidence: 99%
“…50 Via subcortico-cortical circuits, the STN is connected with the anterior cingulate cortex. 51 STN DBS seems to modulate anterior cingulate cortex activity in a task-specific manner 27,52 and might influence spatial orientation via the projections to anterior cingulate cortex of the right hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…Previous fMRI studies on dimension changes found significant activation of multiple posterior brain areas (e.g., Pollmann et al, 2000: fusiform gyrus, lateral occipital gyrus, superior/middle temporal gyrus, SPL and precuneus; Pollmann et al, 2006: IPS, fusiform gyrus, striate/peristriate cortex and posterior putamen/claustrum) that have been implicated in early attentional processes (Corbetta et al, 1993(Corbetta et al, , 1995(Corbetta et al, , 2000Corbetta & Shulman, 1999;Kelley et al, 2008;Macaluso et al, 2000;Nobre et al, 1997, Vandenberghe et al, 2000Yantis et al, 2002). Hence, it was concluded that dimension changes interfere with attention shifts to the target.…”
Section: Theoretical Implicationsmentioning
confidence: 99%